Cover Picture: Oxidation and Reduction Pathways in the Knowles Hydroamination via a Photoredox‐Catalyzed Radical Reaction (Angew. Chem. Int. Ed. 1/2023). Issue 1 (22nd December 2022) - Harabuchi, Yu; Hayashi, Hiroki; Takano, Hideaki; Mita, Tsuyoshi; Maeda, Satoshi
Abstract : Systematic reaction path exploration revealed the entire mechanism of Knowles' light‐promoted catalytic intramolecular hydroamination via radical processes. In their Research Article (e202211936 ), Yu Harabuchi, Satoshi Maeda, and co‐workers investigated the energetically favorable reaction path by constructing reaction path networks and searching for the seam of crossing geometries. Calculations showed that the reduction and proton shuttle process proceeded concertedly.